Saccade Eye Movements as Measure of Frontostriatal Dysfunction in ADHD - J Gordon Millichap (Pediatric Neurology Briefs Publishers, 2010)
Saccade latency and accuracy were tested in 50 normal subjects (6-35 years), 19 ADHD patients (6-11 years), and 4 patients with frontal lesions (13-15 years) in an investigation of reflexive/voluntary control of saccades in ADHD, at University of Yamanashi, Japan.